Thorough approach toward cylindrical MMW image reconstruction using sparse antenna array. Issue 8 (1st August 2018) - Mandi Sanam, Pourya; Seyyed Talebi, Mohammad Javad; Kazemi, Mahmoud; Kavehvash, Zahra; Shabany, Mahdi
Abstract : In this study, a thorough analysis of image reconstruction in an active millimetre‐wave (MMW) cylindrical imaging system is performed. To improve the system's performance in terms of the total cost as well as the coupling effect, sparse multi‐static arrays are desired. Nevertheless, the existing reconstruction methods fail to operate in sparse multi‐static antenna‐array systems. Therefore, to address these shortcomings, in this study, at first, the existing MMW mono‐static cylindrical image reconstruction methods are modified in both single‐frequency and wideband reconstruction platforms. Moreover, in order to further improve the image quality and the system cost, a sparse multi‐static one‐dimensional antenna array has been proposed. To use this sparse array in the cylindrical MMW imaging system, a novel multi‐static cylindrical image reconstruction method is also proposed. The performances of the proposed reconstruction methods for both mono‐static and sparse multi‐static cylindrical imaging structures are validated through numerical simulations. Through the obtained results, 83% reduction in antenna array cost along with a 25 dB decrease in coupling effect is achieved at the cost of a minor reduction in the reconstructed image quality.